2008
DOI: 10.4315/0362-028x-71.7.1320
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Salmonella and Hygiene Indicators in the 10 Largest Belgian Pig Slaughterhouses

Abstract: A survey was conducted to collect data on Salmonella prevalence, Escherichia coli counts (ECCs), and aerobic bacteria colony counts (ACCs) on pig carcasses after chilling at the 10 largest Belgian pig slaughterhouses during 2000 through 2004. Potential risk factors of contamination associated with production parameters, technical descriptions of the installations, and cleaning and disinfection methods were assessed during investigations in the slaughterhouses. These variables were used first in a univariate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…Carcass contamination essentially results not only from the carriage of pathogens by the pig itself, but also from contact with other contaminated carcasses and/or surfaces in the abattoir. Hygiene varies between abattoirs and has been shown to have an important impact on carcass contamination (Baptista et al, 2010;Botteldoorn et al, 2004;Delhalle et al, 2008;Eblen et al, 2006), in addition to pre-slaughter transportation and lairage/holding, which have been shown to increase the contamination risk of the abattoir's slaughter and processing lines (Hurd et al, 2002;Rostagno et al, 2003).…”
Section: On-farm Risk Factorsmentioning
confidence: 99%
“…Carcass contamination essentially results not only from the carriage of pathogens by the pig itself, but also from contact with other contaminated carcasses and/or surfaces in the abattoir. Hygiene varies between abattoirs and has been shown to have an important impact on carcass contamination (Baptista et al, 2010;Botteldoorn et al, 2004;Delhalle et al, 2008;Eblen et al, 2006), in addition to pre-slaughter transportation and lairage/holding, which have been shown to increase the contamination risk of the abattoir's slaughter and processing lines (Hurd et al, 2002;Rostagno et al, 2003).…”
Section: On-farm Risk Factorsmentioning
confidence: 99%
“…The Enterobacteriaceae family comprises a large number of organisms, not all of faecal origin, and are more useful as an indicator of overall process hygiene in the abattoir. E. coli are considered to be a more suitable choice of indicator as they are a single species more specifically associated with faeces (Delhalle et al, 2008;Ghafir, China, Dierick, De Zutter, & Daube, 2008;McEvoy et al, 2004). Studies have found that the presence of E. coli on carcasses were a reliable index for enteric zoonotic agents such as Salmonella (Delhalle et al, 2008;Ghafir et al, 2008).…”
Section: Visitmentioning
confidence: 99%
“…Recently, a survey was carried out in the ten largest Belgian pig slaughterhouses (Delhalle et al, 2008). The carcasses were sampled in the chilling room two to four hours after slaughter.…”
Section: Remarksmentioning
confidence: 99%
“…Monitoring of critical points, the condition and cleanliness of equipment, good slaughtering practices, and effective cleaning and disinfection of equipment were considered as the key elements contributing to food safety during the slaughter process (Delhalle et al, 2008).…”
Section: Intervention Studiesmentioning
confidence: 99%
See 1 more Smart Citation